PENGARUH GCG, RASIO KEUANGAN, ARUS KAS DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS PADA PERBANKAN - Indah Damayanti; Roro Endah Kumalasari; Sana Sholihah (STMIK Mardira Indonesia, Bandung, 2021)
This research examines the effect of GCG, financial ratios, cash flow and company size on financial distress in banks listed on the Indonesia Stock Exchange in 2015-2020. The general objective of this study is to determine how the influence of GCG, financial ratios, cash flow and company size on financial distress in banks listed on the Indonesia Stock Exchange in 2015-2020. Meanwhile, for the specific purpose of this study, it is to analyze more deeply about financial distress, especially in the banking sector, where during the Covid-19 pandemic the risk of financial distress in banks is high. The research method used in this research is to use quantitative analysis. The analytical tools used are descriptive statistics and panel data regression analysis. The population in this research are banks listed on the Indonesia Stock Exchange in 2015-2020. The sampling method in this study used the saturated sampling method. Based on the results of purposive sampling, there are 37 banks that fall into the criteria with an observation period of 2015-2020. The data collection technique used is literature study through various literatures and the internet. Based on the results of the research, it shows that GCG, financial ratios (ROE, ROA, LDR and NPL) and company size have no significant effect on financial distress. Meanwhile, financial ratios (BOPO and NIM) and cash flow have a significant effect on financial distress. Keywords : GCG, Financial Ratios, Cash Flow, Company Size, Financial Distress.